FOREST AND LAND FIRE POLICY IN RIAU PROVINCE; CASE STUDY IN ROKAN HILIR REGENCY - Dede Komala Sari; Nurul Qomar; M. Mardhiansyah (Jurnal Ilmu Ilmu Kehutanan, 2022)
Rokan Hilir Regency was the area with the highest number of hotspots in the last nine years in Riau Province. Combating forest and land fires in areas that require effective policies. The purpose of this study was to study forest and land fire prevention policies in Riau Province, especially in Rokan Hilir Regency. The research sample used qualitative research, the informants were selected by snowball sampling. Primary data were collected through in-depth interviews, field observations and document studies. Data were analyzed descriptively qualitatively. Research Results Shows Research Regarding the Determination of Forest and Natural Forest Disaster, Riau Provincial Regulation No. 1 of 2019 concerning Technical Guidelines for Combating Forest and Land Fires was only adopted on August 15, 2019. For in Rokan Hilir District there was no Regional Regulation governing the destruction of forests and land. However, the Government of Rokan Hilir Regency issued Rokan Hilir Regent's Regulation No. 41 of 2017 concerning the Implementing Unit of Rokan Hilir District Forest and Land Fire Control, in this Regent Regulation, asking for approval, while in Riau Province Regional Regulation No. 1 of 2019 does not provide a deterrent effect for forest and land burners